On the Riesz Basisness of Systems Composed of Root Functions of Periodic Boundary Value Problems - Alp Arslan Kıraç (Abstract and Applied Analysis)
We consider the nonself-adjoint Sturm-Liouville operator with q∈L1[0,1] and either periodic or antiperiodic boundary conditions. We obtain necessary and sufficient conditions for systems of root functions of these operators to be a Riesz basis in L2[0,1] in terms of the Fourier coefficients of q.